Catheter-directed computed tomography angiography: A pictorial essay - Ghosh, Abheek; Moxley, Ellen; Waghmarae, Suneet; Stoner, James; Anand, Sheena; Akhter, Nabeel M. (Journal of Clinical Imaging Science)
Catheter-directed computed tomography angiography (CDCTA) is an imaging technique where CT images are acquired after selective catheterization of a vessel. Images obtained in this fashion provide several advantages over conventional imaging techniques such as fluoroscopic angiography, digital subtraction angiography, cone-beam CT, and conventional CT angiography. At this point, there is still limited literature on the subject, with prior studies examining a small number of potential uses. The goal of this pictorial essay is to illustrate our single tertiary care center experience using CDCTA.